Tetumbuhan Riparian di Situ Cikaret, Kecamatan Cibinong, Kabupaten Bogor, Jawa Barat - Priyanti, Priyanti; Sulistianingsih, Norma; Yunita, Etyn (BIOEDUSCIENCE, 2019)
Abstract The Cikaret lake is one of the areas in Cibinong District, which is the most widely around 16.90 Ha. This study aimed to inventory and identify plants in the riparian area where Cikaret had undergone land conversion to residential and tourist areas. Land conversion in riparian areas would have an impact on the presence of surrounding plants that played an important role in the conservation of soil, water, and living things around them. The study used line transect method to follow the edge or riparian. Observations are made by exploring the riparian land which is limited to a distance of about 5 m away from the edge. Identification of plants is carried out directly at the observation site. Stature of various plants observed was recorded directly at the observation site. The results of the study obtained 45 species of plants belonging to 42 genera and 21 families. The most members are Euphorbiaceae with their species, namely Acalypha siamensis, Celosia argentea, Euphorbia hirta, Manihot esculenta, M. glaziovii, and Phyllantus urinaria. Other tribes consist of 1 to 5 species. The highest percentage of plant stature is occupied by herbs as much as 50%, while other plant stature is shrubs as much as 7%, shrubs as much as 9%, and trees as much as 36%. Plants that lived in the Cikariet Situ riparian area in Cibinong District, Bogor Regency are classified as weeds, agricultural crops, and invasive species.